2007
DOI: 10.1097/iop.0b013e318050d2d1
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Mucous Membrane Grafts: A Histologic Study of Hard Palate, Nasal Turbinate, and Buccal Mucosal Grafts

Abstract: Full-thickness mucosal grafts typically maintain their native epithelial morphology following transplantation to the ocular surface. Submucosal glands usually do not survive transplantation, which could be the result of intentional thinning of the graft at the time of transplantation. Contrary to the opinion that hard palate graft epithelium usually undergoes metaplasia from keratinized to nonkeratinized within 6 months following transplantation to the eye, all hard palate grafts in this study remained orthoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Biopsy of buccal mucosal grafts shows a nonkeratinized, stratified squamous epithelium, consistent with its native morphology, whereas hard-palate grafts remain orthokeratotic or parakeratotic [5]. In this study, we found that buccal mucosal graft was effective in the treatment of moderately exposed hydroxyapatitis orbital implants.…”
Section: Commentsmentioning
confidence: 51%
“…Biopsy of buccal mucosal grafts shows a nonkeratinized, stratified squamous epithelium, consistent with its native morphology, whereas hard-palate grafts remain orthokeratotic or parakeratotic [5]. In this study, we found that buccal mucosal graft was effective in the treatment of moderately exposed hydroxyapatitis orbital implants.…”
Section: Commentsmentioning
confidence: 51%
“…23 Although hard palate mucosal grafts have been successfully used in many studies, a recent report indicates that these grafts stay keratinized for long periods of time. 50 Furthermore, 10% of patients in one large study experienced donor site hemorrhaging that required postoperative interventions including surgery and mouthguards. 49,75,76 Other complications, including oronasal palatal fistula, oral candidiasis, and salivary gland secretion, have been described as well.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of synthetic materials including polytetrafluoroethylene 29,30 and porous polyethylene 31-34 has also been described. Autogenous and irradiated tarsus, [35][36][37][38] donor sclera, 39,40 dermis grafts, 41 auricular cartilage, 20,42-45 cadaveric dermal collagen, 1 and hard palate mucosal grafts 1,3,4,22,23,[46][47][48][49][50] have also been used with varying success rates. The auricular cartilage and hard palate mucosal grafts have probably enjoyed the most use.…”
mentioning
confidence: 99%
“…2 The decision of which graft to use depends on the needs of the patient and surgeon preference. In addition, each graft is associated with potentially significant donor site morbidity, including discomfort and bleeding, and persistent dryness in the nose.…”
Section: Discussionmentioning
confidence: 99%